2023
DOI: 10.2147/jmdh.s411840
|View full text |Cite
|
Sign up to set email alerts
|

Medication Administration Error Perceptions Among Critical Care Nurses: A Cross-Sectional, Descriptive Study

Majdi M Alzoubi,
Asmaa Al-Mahasneh,
Khalid Al-Mugheed
et al.

Abstract: Purpose This study aimed to investigate the medication administration error perceptions among Jordanian critical care nurses. Methods A cross-sectional, descriptive design was used among Jordanian critical care nurses. The total number of completed questionnaires submitted for analysis was 340. Data were collected between July and August 2022 in two health sectors (governmental hospitals and educational hospital) in the middle and north region in Jordan through a self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Furthermore, there was a signi cant statistical relationship between work experience, participation in medication error workshops, and perception of medication errors, which is consistent with the studies byKhalid Al-Mugheed et al (2023) and Wondmieneh et al (2019), but not with the study by Kermanshahi et al (2016)(42)(43)(44). This difference may be due to the type of department and other relevant factors, as their research was speci cally conducted on pediatric nurses.In addition, in this study, a signi cant statistical relationship was found between marital status and perception of medication errors, which is consistent with the study by Saedi et al (2020), but not with the study by Aghili Dehkhordi et al (2019) (45, 46).Stepwise multiple linear regression analysis showed that "patient-centered medication management" was a stronger predictor of medication safety competency and perception of medication errors compared to other variables, which is consistent with the studies by Bijani et al (2024) and Salmani et al (2018)(33,47).Furthermore, in this study, there was a direct and signi cant relationship between the scope of risk management and perception of medication errors, which is consistent with the study by Dehghan Nayeri et al (2021).…”
supporting
confidence: 85%
“…Furthermore, there was a signi cant statistical relationship between work experience, participation in medication error workshops, and perception of medication errors, which is consistent with the studies byKhalid Al-Mugheed et al (2023) and Wondmieneh et al (2019), but not with the study by Kermanshahi et al (2016)(42)(43)(44). This difference may be due to the type of department and other relevant factors, as their research was speci cally conducted on pediatric nurses.In addition, in this study, a signi cant statistical relationship was found between marital status and perception of medication errors, which is consistent with the study by Saedi et al (2020), but not with the study by Aghili Dehkhordi et al (2019) (45, 46).Stepwise multiple linear regression analysis showed that "patient-centered medication management" was a stronger predictor of medication safety competency and perception of medication errors compared to other variables, which is consistent with the studies by Bijani et al (2024) and Salmani et al (2018)(33,47).Furthermore, in this study, there was a direct and signi cant relationship between the scope of risk management and perception of medication errors, which is consistent with the study by Dehghan Nayeri et al (2021).…”
supporting
confidence: 85%
“…[7,8] Although nurses are crucial partners in the healthcare sector and among the frontline healthcare practitioners required to achieve effective healthcare-related programs, numerous challenges confronting hospitals today are frequently attributed to a lack of nurses' commitment and performance, given that nurse commitment is a critical issue in achieving overall hospital performance and pursuing the delivery of an effective healthcare system. [9][10][11][12] Commitment is strongly related to performance because committed nurses engage in more extra-role activities and behaviors such as creativity and innovation. [13] Nurses' dedication and performance have long been recognized as quality service determinants for patients admitted to hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings parallel the literature surrounding personal feelings (i.e., shame, guilt, and scrutiny by others). 7,19,20 Other studies have shown that reporting medication errors was influenced by the potential or actual fear of stigma or damage to professional reputation. 8,9 Peer criticism also played an important role in error reporting, discouraging reporting among nurses.…”
Section: Discussionmentioning
confidence: 99%